The Complexities of Establishing Transboundary Water Management Institutions in Post-Colonial Territories: A Study of Nile River TWMI Construction - Nurridho Aryawan (Andalas Institute of International Studies UNAND, 2024)
Transboundary Water Management Institutions (TWMI) are traditionally seen as comprehensive solutions for addressing the distribution of transnational river water resources, among other alternative strategies. TWMI plays a crucial role in redirecting the potential for conflict in transnational rivers towards more constructive and cooperative outcomes. However, the establishment of TWMI is fraught with challenges, particularly due to the 'limited' nature of available water resources and geopolitical tensions among riparian states. This article argues that the obstacles to forming TWMI under certain conditions extend beyond geopolitical factors and resource limitations. In former colonial territories, the complexities hindering the creation of TWMI are further compounded by the enduring legacy of colonialism and the post-independence needs of these riparian nations. Using the Nile River as a case study and employing Comparative Political Theory (CPT) as a research method, this paper illustrates how colonial legacies in riparian states not only exacerbate but also perpetuate the challenges in establishing Transboundary Water Management Institutions. This article highlights the underexplored impact of colonial legacies on the discourse of multilateral institutional building and international relations among postcolonialism countries, which continue to shape the process of forming international organizations responsible for managing shared natural resources across countries.